Effects of nitrogen fertilization on growth and yield of diterpene glycosides in stevia (Stevia rebaudiana Bertoni) - Debarba, Romulo Joao; Deschamps, Cícero; Kanis, Luiz Alberto; Moterle, Diego; Rampelotti, Marcio (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2021)
The effects of different nitrogen doses on dry weight yield, stevioside and rebaudioside A contents, and yields were evaluated in stevia (Stevia rebaudiana Bertoni). This study was carried out at the Instituto Federal Catarinense, Rio do Sul (SC), Brazil, under decreasing photoperiods. A randomized complete block design with four blocks and five treatments (0, 65, 135, 200 and 270 kg ha-1 N) was used. Variables related to dry weight yield (total dry weight, leaf dry weight, stem dry weight, number of secondary branches and tertiary branches, and main stem length), growth rates (total leaf area, leaf area index, specific leaf area, leaf area ratio, leaf weight ratio), and stevioside and rebaudioside A contents and yields were evaluated. The doses of nitrogen fertilization did not affect the variables related to dry weight yield, stevioside and rebaudioside A contents and yields, or rebaudioside A:stevioside ratio in stevia genotype 8 (G8), grown under decreasing photoperiods.